ORGANIZATION OF ICT DEVELOPMENT PROCESSES IN UZBEKISTAN - Abdullaev Sharof Abdugafforovich (Galaxy International Interdisciplinary Research Journal, 2021)
The article discusses the issues of effective organization of ICT development processes in Uzbekistan. Scientifically based proposals and conclusions were also developed to further improve this situation.